Platinum-bearing chromite layers are caused by pressure reduction during magma ascent - Latypov, Rais; Costin, Gelu; Chistyakova, Sofya; Hunt, Emma J.; Mukherjee, Ria; Naldrett, Tony (Nature Research, 2018)
Platinum-bearing chromitites in mafic-ultramafic intrusions such as the Bushveld Complex are key repositories of strategically important metals for human society. Basaltic melts saturated in chromite alone are crucial to their generation, but the origin of such melts is controversial. One concept holds that they are produced by processes operating within the magma chamber, whereas another argues that melts entering the chamber were already saturated in chromite. Here we address the problem by examining the pressure-related changes in the topology of a Mg2SiO4–CaAl2Si2O8–SiO2–MgCr2O4 quaternary system and by thermodynamic modelling of crystallisation sequences of basaltic melts at 1–10 kbar pressures. We show that basaltic melts located adjacent to a so-called chromite topological trough in deep-seated reservoirs become saturated in chromite alone upon their ascent towards the Earth’s surface and subsequent cooling in shallow-level chambers. Large volumes of these chromite-only-saturated melts replenishing these chambers are responsible for monomineralic layers of massive chromitites with associated platinum-group elements.
Keywords: Magma ascent; Platinum-bearing chromitites; Chromite; Metals; SDG-17: Partnerships for the goals